Material didático digital, games e gamification: conexões no design para implementação de cursos online - Gomes, Adilson Fernandes (2017)
Recent studies highlight the use of digital games and game design elements in the educational context (GEE, 2005; VAN ECK 2006, DETERDING, 2011; ERENLI, 2013; ALVES; MINHO; DINIZ, 2014; BUSARELLO, 2016), however few are the Brazilian studies that associate design, gamification and language teaching. In order to face this gap, this research aims at developing a proposal of design with gamification for distance learning based on the Digital teaching material production Cycle (REIS; GOMES, 2014), the use of intrinsic and extrinsic elements of digital games (LOPES; TODA; BRANCHER, 2015) and the definition of design proposed by Filatro (2008). To do it, we developed a gamified design model to promote the engagement and motivation of participants in solving activities, both to guide actions in face-to-face or blended/distance learning. This study takes part on the Postgraduate Professional Master´s Program in Networked Educational Technologies (PPGTER), in the research line Development in networked educational technologies. In this sense, an exploratory investigation was carried out which includes a bibliographical research and three case studies. The research´s participants were teachers in initial and continuing education from Santa Maria/RS. The literature review provided theoretical support and the case studies give practical support for the development of gamification design. The studies were applied in an undergraduate course; in a module of an extension course and in the extension course “Games and Gamification in the Language teaching”. The instruments used for data collection consist of diagnostic and evaluative questionnaires applied during practical experiments, notes from the tutor’s reflective journal, filming in certain practical experiences, interactions, digital didactic material, activities and reports generated in Moodle. The results evidenced the acceptability of the games and gamification theme by the participants, as well as the testing of the pilot study on gamification design. In addition, we provided direct information on content, didactic activities, load-hour adjustment, and the approval of the elaborated design model. Also, the data indicate that the application of the gamification design model was important to stimulate, motivate and engage the participants in the execution of the activities, while showing a certain discontent regarding the release of digital teaching material in a non-linear format, since it makes use of peripheral connections, because it is not release in a traditional way. The participants indicate the preference for a traditional vertical flow model to access to content, as it is in traditional distance courses. In addition to this dissertation, as a final product we propose the gamification design model for online courses based on five distinct stages, which include the study language design; the selection of didactic content; technological resources; the network of peripheral connections; and the gamification system. We understand that this model can contribute with the academic community and teachers interested in using this design in online courses, since it is an innovative proposal, non-linear presentation of content, exploring elements of design of digital games, that is different from existing traditional distance learning models.